Analisis 16s rDNA-mtDNA sebagai marka genetik variabilitas pertumbuhan ikan kerapu macan (Epinephelus fuscoguttatus) melalui metode PCR-RFLP=Analysis of 16srDNA-mtDNA as variability growth genetic marker ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Groupers are an important commercial fish species in Indonesia and popular marine food fish of high market value in many parts of the world. The objective of this study was to find the genetic marker which can be used as indicator variability of brown marbled grouper fries. The study was conducted at biotechnology laboratory, Research institute for Mariculture on Bali. The initial study were selecting of fish fry based on the total length and body weight. The average total length of the large, medium, and small larvae were 63.27Â±2.62 mm, 50.64Â±1.15 mm